The Syntagma Musicum of Michael Praetorius Volume Three: An Annotated Translation - Praetorius, Michael 1571-1621; Lampl, Hans; Boudreaux, Margret (USA American Choral Association, 2001)
Michael Praetorius (1571-1621) was one of the most versatile, wide-ranging, and prolific German composers of the seventeenth century. Also important as a theorist, his Syntagma Musicum, penned around 1619, was originally planned in four parts. He completed only three, with the first discussing the place of music in the church, while Volume II focused on musical instruments. Volume III deals with terminology, theoretical issues, and performance practice.
Keywords: Music theory